Metodología para la conservación de vías principales de Primer orden con pavimento rígido mediante criterios de Índice de condición del pavimento y análisis de variable térmico, en ciudades de hasta 300.000 habitantes - Del Rosario Villafuerte, Pamela Del Cisne (Machala; Universidad Técnica de Machala, 2024)
The purpose of this work is to develop a methodology for first order road maintenance using surface condition and thermal variable criteria, in cities up to 300,000 inhabitants. of first order roads using surface condition and thermal variable criteria, in cities of up to 300,000 inhabitants, the ASTM-D-6433 standard, together with the research carried out in road evaluation based on roadroid PCI and IRI measurement..., developed by Putra and Suprapto, 2018, the application of a pavement management system based on the use of a geographic information system, developed by Palma et al, 2023, Stress analysis in whitetopping type concrete pavements : case study via Biblián-Zhud de Bojorque-Iñeguez, 2021, are the basis for the methodological design. The methodology proposes to respond to a lack of research in the technical verification system for pavement maintenance. the problem that has been observed in the main roads is a lack of technical verification for the maintenance of rigid pavements. The problem that has been observed in the main roads is an excessive deterioration of the road structures, due to the fact that a control system, road inventory, intervention programs applicable to the physical reality of the road are not implemented, for which the question is asked: What road maintenance methodology guarantees the conservation of the rigid pavement in main roads? The information was collected in the field and was obtained from Km 37 to Km 38 of one of the main roads entering the city of to one of the main entrance roads to the city of Machala, in order to obtain a baseline on the current state of the road, by making an inventory current state of the road by conducting a road inventory based on the form proposed by the ASTM-D-6433 standard. by the ASTM-D-6433 standard, in order to evaluate and diagnose the surface condition of the pavement the surface condition of the pavement (ICP), information was obtained from the Autonomous Government and the Ministry of Transportation and Theoretical correlations were developed to determine the thermal gradient of rigid pavement slabs and the coefficient of thermal expansion, which helped to evaluate the pavement structure with the help of the EvereFe program. Using the ICP and ΔT criteria, a methodology was developed to evaluate the surface condition and assess the pavement structure. surface condition and pavement structure assessment methodology was developed to establish which slabs should be the pavement structure to establish which slabs should be rehabilitated or reconstructed and the development of the road maintenance program. maintenance program
El presente trabajo tiene como propósito desarrollar una metodología para conservación de vías de primer orden mediante criterios de condición superficial y variable térmico, en ciudades de hasta 300.000 habitantes, la norma ASTM-D-6433, junto con las investigaciones realizadas en la evaluación de la carretera basada en la medición de roadroid PCI e IRI., desarrolladas por Putra y Suprapto, 2018, la aplicación de un sistema de gestión de pavimentos basado en el empleo de un sistema de información geográfica, desarrollados por Palma et al, 2023, Análisis de esfuerzos en pavimentos de concreto tipo whitetopping . caso de estudio vía Biblián-Zhud de Bojorque-Iñeguez, 2021, son la base para el diseño metodológico. La metodología propone dar respuesta a una falta de investigación en el sistema de verificación técnica para el mantenimiento de pavimentos rígidos, el problema que se ha observado en las vías principales es un deterioro excesivo de las estructuras viales, debido a que no se implementa un sistema de control, inventario vial, programas de intervención aplicable a la realidad física de la vía, para lo cual se realiza la interrogante: ¿Qué metodología de mantenimiento vial, garantiza la conservación del pavimento rígido en vías principales?. La información fue recolectada en campo se obtuvo del Km37 al Km 38 de una de las vías principales de ingreso a la ciudad de Machala, para obtener bases en referencia al estado actual de la vía realizando un inventario vial basado en el formulario propuesto por el norma ASTM-D-6433, para poder evaluar y diagnosticar la condición superficial del pavimento (ICP), se obtuvo información del Gobierno Autónomo y el Ministerio de Transporte y Obras Públicas recogiendo información histórica de los estudios ejecutados y las intervenciones realizadas, con la investigación bibliográfica y de campo respecto al temperatura ambiente de la ciudad de Machala tomados del INAMHI, se desarrollaron correlaciones teóricas para determinar el gradiente térmico de las losas de pavimento rígido y el coeficiente de expansión térmica, que ayudaron a evaluar la estructura del pavimento con la ayuda del programa EvereFe. Con los criterios de ICP y ΔT, se desarrolló una metodología de evaluación de la condición superficial y evaluación de la estructura del pavimento para establecer que losas deben ser intervenidas para su rehabilitación o reconstrucción y el desarrollo del programa de mantenimiento vial
Keywords: MANTENIMIENTO VIAL; CONSERVACION VIAL; INDICE DE CONDICION DEL PAVIMENTO; GRADIENTE TERMICO